Pemanfaatan Antibodi Monoklonal dalam I-ELISA untuk Deteksi Penyebab Penyakit Busuk Pucuk Kelapa (Phytophthora palmivora) - Susamto Somowiyarjo; Daisy Prapto Sriyanti; Mulyadi Mulyadi; Suryanti Suryanti; Y. M.S. Maryudani; Bambang Hadisutrisno (Jurnal Perlindungan Tanaman Indonesia, 1999)
Mice monoclonal antibodies (MCAs) against Phytophthora palmivora, Butl. (the pathogen of coconut bud rot) have been produced and tested. The selected hybridoma (Ab-PM.3) secreted monoclonal antibodies of IgM subclass and the titer in vitro of 10^2 - 1O^3, was employed to develop Indirect-Enzyme Linked lmmunosorbent Assay. This assay was able to differenciate coconut isolate of P. palmivora not only from cocoa and pepper isolate of the same species, but also from other fungus isolated from coconut bud rot diseased coconut (Fusarium sp., Colletotrichum sp., and Thielaviopsis sp.). This assay was able to differenciate P. pulmivora isolate from diseased coconut with those isolated from cocoa and pepper, and other fungus isolated from diseased coconut, thereby providing specific diagnostic tool for coconut bud rot which is needed for supporting the application of the concept of integrated pest mangement on coconut.